Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 33978 by abdo imad last updated on 28/Apr/18

let f(t) = ∫_0 ^∞    ((sin(x^2 )e^(−tx^2 ) )/x^2 ) dx       with t>0  find a simple form of f^′ (t) .

letf(t)=0sin(x2)etx2x2dxwitht>0 findasimpleformoff(t).

Commented bymath khazana by abdo last updated on 01/May/18

after verifying condition of derivabity for f we have  f^′ (t) =∫_0 ^∞ −x^2    ((sin(x^2 )e^(−tx^2 ) )/x^2 )dx  =−∫_0 ^∞  sin(x^2 ) e^(−tx^2 ) dx ⇒ 2 f^′ (x)= −∫_(−∞) ^(+∞)  sin(x^2 )e^(−tx^2 ) dx  =Im(∫_(−∞) ^(+∞)   e^(−ix^2 )  e^(−tx^2 ) dx) but  ∫_(−∞) ^(+∞)    e^(−ix^2 ) e^(−tx^2 ) dx = ∫_(−∞) ^(+∞)    e^(−(t +i)x^2 ) dx  =_((√(t+i))x=u)  ∫_(−∞) ^(+∞)    e^(−u^2 )  (du/(√(t+i))) = ((√π)/(√(t+i)))  but  ∣t+i∣=(√(1+t^2  ))   ⇒t+i =(√(1+t^2 ))( (t/(√(1+t^2 ))) +(i/(√(1+t^2 ))))  =r e^(iθ)  ⇒r=(√(1+t^2 ))   and cosθ= (t/(√(1+t^2 )))  and   sinθ =(1/(√(1+t^2 ))) ⇒tanθ= (1/t) ⇒θ=arctan((1/t))  t+i =(1+t^2 )^(1/2)  e^(i((π/2)−arctant))  ⇒  (√(t+i))= (1+t^2 )^(1/4)   e^(i( (π/4) −(1/2)arctant))   (1/(√(t+i))) = (1+t^2 )^(−(1/4))   e^(i((1/2)arctant−(π/4)))  ⇒  2f^′ (x)= (1+t^2 )^(−(1/4))   sin((1/2)arctant −(π/4)) ⇒  f^′ (x) = (1/2) (1+t^2 )^(−(1/4))  sin((1/2) arctant −(π/4)) .

afterverifyingconditionofderivabityforfwehave f(t)=0x2sin(x2)etx2x2dx =0sin(x2)etx2dx2f(x)=+sin(x2)etx2dx =Im(+eix2etx2dx)but +eix2etx2dx=+e(t+i)x2dx =t+ix=u+eu2dut+i=πt+ibut t+i∣=1+t2t+i=1+t2(t1+t2+i1+t2) =reiθr=1+t2andcosθ=t1+t2and sinθ=11+t2tanθ=1tθ=arctan(1t) t+i=(1+t2)12ei(π2arctant) t+i=(1+t2)14ei(π412arctant) 1t+i=(1+t2)14ei(12arctantπ4) 2f(x)=(1+t2)14sin(12arctantπ4) f(x)=12(1+t2)14sin(12arctantπ4).

Commented bymath khazana by abdo last updated on 01/May/18

f^′ (t)= (1/2)(1+t^2 )^(−(1/4))  sin((1/2) arctant −(π/4)) .

f(t)=12(1+t2)14sin(12arctantπ4).

Answered by candre last updated on 30/Apr/18

f(t)=∫_0 ^∞ ((sin x^2 e^(−tx^2 ) )/x^2 )dx  lets use the fact that  ∫_(−∞) ^(+∞) e^(−ax^2 ) dx=(√(π/a))  sin x=((e^(ix) −e^(−ix) )/(2i))  we get  (df/dt)=∫_0 ^∞ (∂/∂t)((sin x^2 e^(−tx^2 ) )/x^2 )dx  =−∫_0 ^∞ sin x^2 e^(−tx^2 ) dx  =−∫_0 ^∞ ((e^(ix^2 ) −e^(−ix^2 ) )/(2i))e^(−tx^2 ) dx  =−(1/(2i))[∫_0 ^∞ e^((i−t)x^2 ) dx−∫_0 ^∞ e^(−(i+t)x^2 ) dx]  =((√π)/(4i))((√(1/(t+i)))−(√(1/(t−i))))

f(t)=0sinx2etx2x2dx letsusethefactthat +eax2dx=πa sinx=eixeix2i weget dfdt=0tsinx2etx2x2dx =0sinx2etx2dx =0eix2eix22ietx2dx =12i[0e(it)x2dx0e(i+t)x2dx] =π4i(1t+i1ti)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com